Language policy, education and ethnic pride cultural marginalization in Philippine education - Sugbo, Victorio N. (Danyag :the UPV journal of humanities and social sciences, 2000)
The paper examines the role of language policy and its implementation in the educational system in the Philippines. It specifically delves into the problems created by the language policy in terms of cultural marginalization and the erosion of the cultural heritage of language groups in the country. Analysis of social studies and language texts used in the educational system reveals that language policy implementation has rendered certain language groups marginal, if not invisible. The policy has further affected the latter's literacy production and development.